A relative power table for nested matched case-control studies. Issue 1 (1st January 1999) - Pang, D
Abstract : OBJECTIVE: To calculate relative powers for nested case-control studies for different values of both relative risk and numbers of controls per case, given a fixed number of cases available for analysis. METHODS: Algebraic and numerical methods. RESULTS: In nested case-control studies, statistical power is a function of relative risk, rarity of exposure, number of case-control sets, and the number of controls per case. CONCLUSION: The dictum that sufficient power will be obtained in a nested case-control study by selecting only four controls per case cannot be sustained. Appropriate numbers need to be calculated for specific studies.